Perlindungan Hukum Perempuan dari Diskriminasi: Analisis Implementasi CEDAW di Daerah Istimewa Yogyakarta - Haris Aulawi, Muhammad; Sarnawa, Bagus; Edwina, Yodia Adriatmi; Wardani, Susilo (Universitas Muhammadiyah Yogyakarta, 2026)
Human Rights (HAM) violations remain a global issue alongside democratic development. Normatively, human rights are inherent gifts from God that must be protected by the state, law, and society to uphold human dignity. As a protection effort, international instruments like the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) exist, which Indonesia ratified through Law No. 7 of 1984. However, despite this ratification, many Indonesian women still face discrimination, harassment, and violence, lacking both physical and psychological security. This research aims to produce an academic paper to implement the protection of women's rights effectively. To achieve this objective, this study employs a normative legal approach, focusing on library research through various documents and treaties. The primary data source is secondary data, which includes laws, regulations, academic papers, articles, dictionaries, and encyclopedias. To complement the secondary data, the researcher conducted open-ended interviews with key resource persons, including the Head of the Yogyakarta Special Region Province Women and Community Empowerment Agency, and representatives from the